(untitled) (Baghdad Science Journal, 2016)
This work comprises the synthesis of new phenoxazine derivatives containing N-substituted phenoxazine starting from phenoxazine (1). Synthesis of ethyl acetate phenoxazine (2) through the reaction of phenoxazine with ethylchloroacetate, which reacted with hydrazine hydrate to give 10-aceto hydrazide phenoxazine (3), then reacted with formic acid to give 10-[N-formyl acetohydrazide] phenoxazine (4). Reaction of compound (4) with phosphorous pentaoxide or phosphorus pentasulphide to gave 10-[N-methylene-1,3,4-oxadiazole] phenoxazine (5) and 10-[N-methylene-1,3,4-thiadiazole] phenoxazine (6).